Using a rigid lens as endocapsular supporting device in cataract surgery for moderate subluxated cataracts - Lai, Ping-Hong; Yang, Jun; Han, Fang (Annals of Eye Science; Vol 3 (June 2018): Annals of Eye Science, 2018)
Background: To present a surgical technique using a rigid intraocular lens as endocapsular supporting device in manual small incision cataract surgery (MSICS) for treating mild-moderate subluxated cataracts. Methods: In our technique, a single-piece rigid polymethyl methacrylate (PMMA) lens was implanted in the bag following the nucleus removal, with its axis vertical to the zonular dialysis. This endocapsular-implanted IOL stretched the bag and provided sufficient stability and lens centration. This technique was performed in 19 eyes with subluxated cataracts, with zonulysis of ≤120 degree and nuclear sclerosis of grade ≤3. Mean follow-up time was 9.8 months. Results: All eyes had endocapsular IOL implantation during surgery. Intraoperative extension of the dialysis did not occur in any eye. The IOL was placed in the bag in all but 1 case, in which dislocation of the IOL haptic into the vitreous occurred. Though the IOL was slightly decentered in 3 cases, it kept stable. All patients were asymptomatic. Conclusions: This approach provides a simplified and practical strategy for surgically managing subluxation with mild-moderate zonular loss.